Anticancer effect of bacteria on cervical cancer: Molecular aspects and therapeutic implications - Pourmollaei, Soraya; Barzegari, Abolfazl; Farshbaf-Khalili, Azizeh; Nouri, Mohammad; Fattahi, Amir; Shahnazi, Mahnaz; Dittrich, Ralf (Life Sciences, 2020)
Cervical cancer is the second common cancer and the third leading cause of cancer deaths among women in less developed countries. It has been indicated that changes in vaginal microbiome play an important role in the occurrence and development of cervical cancer. However, studies have shown that probiotics play an effective role in fighting cancer by affecting pathogenic bacteria, inducing cancer cells apoptosis, and other anticancer activities. Therefore, the purpose of the present study is reviewing the anticancer effect of cervicovaginal bacteria and their potential for cervical cancer treatment.
CRIS-Team Scopus Importer:2020-02-25
Keywords: Bacteria; Cancer; Cancer treatment; Cervix